Victims without voice: a research and intervention program to protect Moroccan minors in the streets of Ceuta - Carvalho da Silva, Jacqueline; García-España, Elisa (My University, 2019)
Due to its geographical location Ceuta faces a big challenge: aside from the 300 unaccompanied minors hosted in the reception center for minors under the tutelage of the protection system there are around 50 minors in street situation. The PREMECE program an agreement between the city of Ceuta and the University of Malaga focus on research and intervention with this group that escapes the protection system. For many of these minors Ceuta is city of passage to Spanish peninsula so they remain on the streets adjoining the port looking for the opportunity to cross the Strait of Gibraltar underneath the trucks that depart on ferries. On the streets of Ceuta they are exposed to victimization and delinquency risks. Under the PREMECE Program a team of educators and psychologists work with the minors on the streets using strategies of positive parenting to help them to make appropriate decisions and leave the street. Through the participant observation and the relationship of trust built between the street educators and the minors it is possible to obtain data on victimization that would not otherwise reach the authorities' knowledge. This presentation is focused on the victimization of this group who is often labeled as delinquent.
Keywords: Menores de edad - Protección, asistencia, etc - Ceuta; Menores marginados - Ceuta; Menores socialmente desfavorecidos - Ceuta; Niños - Protección, asistencia, etc - Ceuta; Victims; Foreign; Unaccompanied minors; Crime; Prevention; Protection